Pengaruh Media Buku Cerita Bergambar Terhadap Kemampuan Membaca Permulaan Siswa Kelas II SD Negeri 10 Pinggir: Penelitian - Anggi Sulistiawati; Febrina Dafit (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of using picture storybook media on the early reading ability of second-grade students at SD Negeri 10 Pinggir. The background of this research is based on the low level of early reading skills among elementary school students, particularly in understanding simple texts. The research employed a quantitative approach with an ex post facto design. The population consisted of all second-grade students, while the sample was selected purposively. The determined sample was class II A, consisting of 29 students. The research instruments included a picture storybook questionnaire and an early reading ability test, both of which had been tested for validity and reliability. Data analysis was carried out using descriptive statistics, prerequisite tests, and inferential statistical analysis. The results showed that the use of picture storybook media had a significant effect on improving students’ early reading ability. Therefore, picture storybook media can be used as an alternative learning tool to support early literacy skills in elementary schools.